Solution:
Given, x=-3, y=6, and z=4
Putting these values in the given equation:
-15+(-x)+y
= -15+(-(-3)+6
= -15+3+6
= -15+9
= -6
Answer:
C
Step-by-step explanation:
congruence means duplicate so you have to see its reflection
Answer:
cant see image ;( sadddddddd
Step-by-step explanation:
Answer:
18
Step-by-step explanation:
awwww this is so sweet of you! you see this is the type of people we need in the world, kind people like you just wanting to help, thats why I answer questions on brainly not for the points and popularity but to help people out, thank you! <33333